Alienation of Labour Regulations in The Job Creation Law With International Human Rights - Firdaus, Muhammad Ihsan; Maswandi, Muhammad Laily; AD., Nasron (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2023)
Job creation regulated in Law 6 of 2023 still leaves legal problems at the norm level, especially regarding workers’ rights. This study analyses the workers’ rights regulations regulated in the International Covenant on Economic, Social, and Cultural Rights 1976 (ICESCR) and the ILO Convention associated with labour clusters. This research uses normative legal research. The results of this study are first, the rights of workers/labourers regulated in the Eco Covenant and the ILO Convention are the right to work, get a decent wage, not forced to work; leave; the right to be free from forced labour; get weekly breaks; and the role of the state represented by the government to guarantee the rights of workers/labourers. Second, there is a discrepancy between the Eco Covenant and the ILO Convention regarding the regulation of labour in the labour cluster, so it is contrary to human rights principles. The state should pay more attention to the provisions of the Eco Covenant and the related ILO Conventions, and the internal regulation of the employment cluster must be inclined to workers/labourers with a lower bargaining position than employers. Cipta kerja yang diatur dalam Undang-Undang 6 Tahun 2023 masih menyisakan permasalahan hukum dalam tataran norma, khususnya dalam wilayah hak pekerja/buruh. Tujuan dari adanya penelitian ini adalah untuk menganalisis peraturan tentang hak-hak pekerja/buruh yang diatur dalam Kovenan Ekosob dan Konvensi ILO yang dikaitkan dengan klaster ketenagakerjaan. Penelitian ini menggunakan penelitian hukum normatif. Hasil penelitian ini adalah pertama, hak-hak pekerja/buruh yang diatur dalam Kovenan Ekosob dan Konvensi ILO adalah hak bekerja; mendapatkan upah yang layak; tidak dipaksa bekerja; cuti; hak terbebas dari kerja paksa; mendapatkan istirahat mingguan; dan peran negara yang direpresentasikan oleh pemerintah untuk menjamin hak-hak bagi para pekerja/buruh. Kedua, terdapat ketidaksesuaian antara Kovenan Ekosob dan Konvensi ILO dengan pengaturan ketenagakerjaan yang diatur dalam klaster ketenagakerjaan, sehingga bertentangan dengan prinsip-prinsip dari hak asasi manusia. Seharusnya negara lebih melihat lagi kepada ketentuan Kovenan Ekosob dan Konvensi ILO yang terkait dan pengaturan dalam pada klaster ketenagakerjaan harus condong kepada pekerja/buruh yang memiliki posisi tawar yang lebih rendah daripada pengusaha.